Afferent renal innervation in anti-Thy1.1 nephritis in rats - Rodionova, Kristina; Veelken, Roland; Hilgers, Karl Friedrich; Paulus, Eva Maria; Linz, Peter; Fischer, Michael J.M.; Schenker, Martina; Reeh, Peter; Tiegs, Gisa; Ott, Christian; Schmieder, Roland; Schiffer, Mario; et al. (American Journal of Physiology-Renal Physiology, 2020)
Afferent renal nerves exhibit a dual function controlling central sympathetic outflow via afferent electrical activity and influencing intrarenal immunological processes by releasing peptides such as calcitonin gene-related peptide (CGRP). We tested the hypothesis that increased afferent and efferent renal nerve activity occur with augmented release of CGRP in anti-Thy1.1 nephritis, in which enhanced CGRP release exacerbates inflammation. Nephritis was induced in Sprague-Dawley rats by intravenous injection of OX-7 antibody (1.75 mg/kg), and animals were investigated neurophysiologically, electrophysiologically, and pathomorphologically 6 days later. Nephritic rats exhibited proteinuria (169.3 ± 10.2 mg/24 h) with increased efferent renal nerve activity (14.7 ± 0.9 bursts/s vs. control 11.5 ± 0.9 bursts/s, n = 11, P < 0.05). However, afferent renal nerve activity (in spikes/s) decreased in nephritis (8.0 ± 1.8 Hz vs. control 27.4 ± 4.1 Hz, n = 11, P < 0.05). In patch-clamp recordings, neurons with renal afferents from nephritic rats showed a lower frequency of high activity following electrical stimulation (43.4% vs. 66.4% in controls, P < 0.05). In vitro assays showed that renal tissue from nephritic rats exhibited increased CGRP release via spontaneous (14 ± 3 pg/mL vs. 6.8 ± 2.8 pg/ml in controls, n = 7, P < 0.05) and stimulated mechanisms. In nephritic animals, marked infiltration of macrophages in the interstitium (26 ± 4 cells/mm2) and glomeruli (3.7 ± 0.6 cells/glomerular cross-section) occurred. Pretreatment with the CGRP receptor antagonist CGRP8-37 reduced proteinuria, infiltration, and proliferation. In nephritic rats, it can be speculated that afferent renal nerves lose their ability to properly control efferent sympathetic nerve activity while influencing renal inflammation through increased CGRP release.
CRIS-Team Scopus Importer:2020-11-13
Keywords: afferent renal neerves; calcitonin gene-related peptide; renal inflammation; renal innervation; sympathetic innervation